P245 Influenza b outbreak at a large adult cf centre: clinical consequences and potential contributing factors. (15th November 2017) - Dennis, JB; Welfare, W; Turner, A; Barry, PJ; Bright-Thomas, RJ
Abstract : Introduction: In May 2016 an outbreak of influenza was declared on the adult cystic fibrosis (CF) ward at the Manchester Adult Cystic Fibrosis Centre (MACFC), where all patients are treated in individual rooms and strongly encouraged not to mix. The aim of this study was to investigate the outbreak, its clinical consequences, and potential contributing factors. Method: Notes of all patients admitted to the CF ward in May 2016 were retrospectively reviewed and data recorded included: patient location, respiratory viral PCR results, spirometry data (baseline measurements in the 6 month prior to onset, at onset of influenza, and at 3 months post infection), influenza vaccination status (all staff and patients), and measurements of ventilation in patient rooms. Results: Ten patients tested positive for influenza B; all were shown to have been infected with the same strain of the virus: B/Brisbane/60/2008. An outbreak timeline identified the likely index case (only patient admitted within the incubation period of influenza, first to develop symptoms and test positive for influenza B). Subsequently, 8 patients whose rooms were in close proximity on the ward to the index case became infected, as did 1 patient at other end of ward. Influenza B infection was followed by an average reduction in FEV1 of 10.54% (SD 11.25) at the time of infection (p=0.0124). Follow-up data demonstrated a persistent FEV1 reduction of 10.50% (SD 5.95) 3 months post infection (p=0.0034). 70% of patients on the ward and 62% of staff had received the seasonal influenza vaccine. Further investigation revealed this to be a trivalent influenza vaccine that did not cover the strain B/Brisbane/60/2008. A ward ventilation survey identified that ventilation measurements in affected patient rooms ranged from 1.75 to 2.10 air changes/hour, well below DOH recommendations of 6 air changes/hour for single patient rooms. Conclusion: The influenza B outbreak at the MACFC had a detrimental effect on patients' lung function, which was still present after 3 months. Inadequate ward ventilation and a lack of protection from the influenza vaccine given to patients and staff may have contributed to the spread of the virus.